Memahami Kembali Konsep khilāfah dalam Sejarah Global - Kamaruzzaman Bustamam Ahmad; Fitri Zulfidar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
This article examines the positioning of the concept of khilāfah in the context of global history. It must be admitted that this concept received a negative response from various groups, especially scholars and governments, which did not allow the power of Islam to emerge ideologically on the global stage. Therefore, various results of geopolitical analysis always assume that the concept of khilāfah is a concept that has a negative impact on the global order. However, as explained in this article, the concept of khilāfah has a very strong theological dimension in Islamic teachings. Therefore, the more it is shunned from being used as an Islamic political force, the stronger the desire of some Muslims to use this concept as an argument and pretext in their system of struggle. Through a bibliographic survey, this article finds that the problem of war or violence in the name of religion is not only triggered by the concept of khilāfah but there are other problems that arise socio-historically and socio-politically, in Muslim countries, where interests Western countries, also play a significant role geopolitically and geo-strategic, in the contestation.